Understanding Chinese international college and university students' physical activity behavior - Zi Yan; Bradley J. Cardinal; Alan C. Acock (Elsevier, 2015)
Objective: To examine factors of the youth physical activity promotion (YPAP) model that are associated with Chinese international students' meeting PA recommendations (MPAR). Methods: A total of 649 (females = 320, males = 329) Chinese international college students participated in the study. This study was conducted in the United States (US.) between June and August in 2011. Participants completed an online survey regarding their demographic, PA, predisposing, enabling, and reinforcing factors. Results: Logistic nested-regression analysis suggested that being male, having a higher body mass index, perceived competence, self-efficacy, attitude, and enjoyment all increased (p < 0.001) the participants' odds of MPAR. Except language barriers, all of the enabling and reinforcing factors predicted MPAR indirectly through the predisposing factors (p < 0.001). Conclusion: Understanding factors that influence PA among Chinese international students is an important step in the process of promoting their long-term health and wellbeing. Designing program that address the identified key factors may help colleges and universities achieve this goal.